“That’s Not Art, It’s Just Consultation!”: Performing Innovation in Socially Responsive Creative Technologies Research - Caines, Rebecca; Watson, Brandon (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This article brings together two perspectives on the field of creative technologies and explores its place in practice-based research. Case studies are drawn from maker culture projects, pedagogical work in developing creative technologies programs in tertiary institutions, and socially engaged art projects taking up creative technologies methodologies. The article also contains an embedded research instructable, with prompts for engaging with communities, arts institutions, and industry. This article shares hopes for creative technologies as a form of practice-based research that can disrupt exclusive art and research cultures to make room for difference and value diverse kinds of innovation.